2021
DOI: 10.1024/0301-1526/a000971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACEI and ARB treatment on nitric oxide-dependent endothelial function

Abstract: Summary: Background: Angiotensin-converting-enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) are widely used as a first-line therapy for the treatment of cardiovascular disease. Here, ACEI modulate the bradykinin receptor (BDKRB1 and BDKRB2) system and NO-dependent endothelial function, thus determining cardiovascular health and regenerative arteriogenesis. The current study aims at evaluating nitric oxide-dependent endothelial function, and gene expression of bradykinin receptors in periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It is well known that ACE and bradykinin receptors are localized in the plasma membrane of brain endothelial cells 18,35 and in regard to monocytes we have recently shown the expression of ACE (and also bradykinin receptor 1 and 2) on peripheral blood mononuclear cells from 165 cardiovascular patients. 36 Thus, we believe that in particular, the B1R signalling pathway significantly controls arteriogenesis by modulation of EC and monocyte migration, and here ACEi accumulated kinins act via a classical B1R agonist binding.…”
Section: Cell Proliferationmentioning
confidence: 89%
“…It is well known that ACE and bradykinin receptors are localized in the plasma membrane of brain endothelial cells 18,35 and in regard to monocytes we have recently shown the expression of ACE (and also bradykinin receptor 1 and 2) on peripheral blood mononuclear cells from 165 cardiovascular patients. 36 Thus, we believe that in particular, the B1R signalling pathway significantly controls arteriogenesis by modulation of EC and monocyte migration, and here ACEi accumulated kinins act via a classical B1R agonist binding.…”
Section: Cell Proliferationmentioning
confidence: 89%
“…Accordingly, using different outcome measures, including FMD, numerous clinical studies have demonstrated the ability of ACE inhibitors and ARBs to improve endothelial function [ 96 , 97 ], even in patients with concomitant coronary artery disease [ 98 ] and either type of diabetes mellitus [ 99 , 100 ].…”
Section: Therapeutic Targets For Endothelial Dysfunction In Hypertensionmentioning
confidence: 99%
“…Here, ECs proliferation and migration are essential for collateral artery formation. It is speculated that novel medications for cardiovascular disease may shift the process of pathologic atherosclerosis toward physiological arteriogenesis (64). Recent research has shown that arterial network expansion complemented collateral arterial development to recover from an ischemic insult, in which endothelial function plays an important role in arterial flow recovery (65,66).…”
Section: Discussionmentioning
confidence: 99%